Introducing a New Technique for Fascial Closure to Avoid Renal Allograft Compartment Syndrome in Pediatric Recipients: The Use of Tutoplast® Fascia Lata - Bañuelos Marco, Beatriz; Bergel, Berenice; Geppert, Tamara; Müller, Dominik; Lingnau, Anja (Frontiers in Surgery, 2022)
Introduction Renal allograft compartment syndrome (RACS) is a complication that infrequently occurs after renal transplantation. Tight muscle closure may lead to RACS due to compression of renal parenchyma or kinking of the renal vessels. Many techniques have been proposed in an attempt to achieve tension-free closure, which can be specially challenging in child recipients. We present our experience with Tutoplast® Fascia Lata (RTI Surgical Tutogen Medical GmbH Industriestrasse 6, 91077 Neunkirchen am Brand, Germany) closure. Methods All pediatric patients who underwent renal transplantation in our center between 2012 and 2021 were reviewed. Eight patients with Tutoplast® Fascia Lata placed at the time of initial transplantation were identified. Donor and recipient characteristics, Doppler ultrasound findings, and overall patient and graft survival rates were analyzed. Results Doppler ultrasound was performed intra-operatively after abdominal wall closure. If any sign of vascular compromise was seen, the abdominal wall was opened and the graft was revised. The Tutoplast® Fascia Lata implant was used to perform tension-free fascia closure and, afterwards, a Doppler ultrasound was performed to confirm the optimal renal artery perfusion and venous patency. Three of the renal transplantations were from a cadaver donor, with two of them en bloc. Living donor transplantation was performed in four cases. Among which, there was a case of auto-transplantation due to bilateral renal artery stenosis. None of the patients presented any complications of either short or long term that was derived from the abdominal closure with Tutoplast® Fascia Lata. There was also no record of graft failure till datum. Conclusions Restricted volume of the recipient pelvic cavity and the size discrepancy between the recipient pelvic cavity space and the donor adult kidney may lead to RACS. Other situations that occur more infrequently, i.e., as en bloc or auto-transplantation, are prone to suffer the same problem. Tutoplast® Fascia Lata is a safe option for these patients.